2023
DOI: 10.52728/ijjm.v4i1.672
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Brand Ambassador and Price Discount on Consumer Purchase Intention in E-Commerce Shopee (Case Study on Shopee Users in Bandung City)

Abstract: The participation of micro, small, and medium-sized enterprises (MSMEs) is one of the elements that can either contribute to or detract from the rate of economic growth in Indonesia. This study incorporates responses from 194 small and medium-sized businesses located within the province as its sample. This study made use of the purposive random sample approach for its data collection, and primary data was the type of data that was analyzed over the course of the study. Structural Equation Modeling (SEM), along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
1
0
1
Order By: Relevance
“…Aiming at halal certification is also less effective if the halal awareness of consumers formed by Make Over is not successful. The findings of this research strengthen previous research where halal certification had no effect on purchase intention (Putra et al, 2023). However, this contradicts research by Aprilia & Saraswati (2021), which concluded that halal certification has a significant and positive effect on purchase intention.…”
Section: Discussionsupporting
confidence: 58%
“…Aiming at halal certification is also less effective if the halal awareness of consumers formed by Make Over is not successful. The findings of this research strengthen previous research where halal certification had no effect on purchase intention (Putra et al, 2023). However, this contradicts research by Aprilia & Saraswati (2021), which concluded that halal certification has a significant and positive effect on purchase intention.…”
Section: Discussionsupporting
confidence: 58%
“…Keputusan pembelian adalah tindakan dari konsumen untuk membeli atau tidak membeli produk [7]. Ada berbagai faktor yang dapat mempengaruhi keputusan pembelian konsumen, diantaranya adalah kualitas produk, citra merek dan faktor harga [8].…”
Section: Pendahuluanunclassified
“…One of the factors that can attract consumers to make purchasing decisions is the company's ability to communicate its brand (branding) or promotion (promotion) and brand image. One method that is currently popular for brand building, and is used in various business fields including by marketplace companies is by introducing products through brand ambassadors, and the promotion method used so that it has an impact on brand image and purchasing decisions (Faritzal et al, 2023;Hartati et al, 2022;Jayusman et al, 2023).…”
Section: Introductionmentioning
confidence: 99%